2018
DOI: 10.1142/s0217979218503642
|View full text |Cite
|
Sign up to set email alerts
|

Trembling motion of the wave packet in armchair graphene nanoribbons (AGNRs)

Abstract: A treatment of the trembling motion or Zitterbewegung (ZB) phenomena in the armchair graphene nanoribbons (AGNRs) by using long-wave approximation is presented theoretically. We are first interested to study the time dependence of the average values for the current density in AGNR. The longitudinal and transversal components of the current density operator are derived analytically in the Heisenberg representation. The wave packet in a Gaussian distribution is considered with half-width d and a carrier wave vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…(2) shows the structure diagram of AGNR armchair graphene nanoribbon with length L and width W . The width is represented by dashed lines on the y-axis of the ribbon, where it is given as a function of two carbon atoms per unit cell [21]:…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) shows the structure diagram of AGNR armchair graphene nanoribbon with length L and width W . The width is represented by dashed lines on the y-axis of the ribbon, where it is given as a function of two carbon atoms per unit cell [21]:…”
Section: Theoretical Modelmentioning
confidence: 99%
“…They emphasized that the coupling between the bulk states and edge states has interesting features, and they also observed that the oscillation in position occurs along the direction of the wave packet propagation which is unavailable in the infinite graphene sheets and semiconductor nanowires. Majid and Savinskii [17,18] and Majid and Alla [19][20][21] analyzed in the detailed description of wave-packet evolution in a monolayer graphene, carbon nanotubes and graphene nanoribbon by using the Heisenberg representation, they investigated the influence of the different pseudospin polarizations on the wave-packet dynamics for the initial wave function and the phenomenon of ZBW. The time evolution of the wave packet in bilayer graphene is investigated theoretically by using the long wave approximation and the Heisenberg representation [22].…”
Section: Introductionmentioning
confidence: 99%